Analysis of the Maxim of Language Courtesy of Geoffrey Leech in the Podcast Study of Ustad Felix Siauw: A Descriptive Study of Da'wah Communication Style in the Digital Era - Atika Zikri; Ngusman Abdul Manaf; Tressyalina (CV. Syntax Corporation Indonesia, 2026)
This study analyzes the application of Geoffrey Leech’s politeness maxims in Ustadz Felix Siauw’s podcast lectures on the YouTube platform. Using a qualitative descriptive method, this research examines how a contemporary Islamic preacher applies the principles of linguistic politeness in delivering da'wah messages to diverse audiences in the digital era. Leech’s politeness maxim theory, consisting of six main maxims—tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim—is used as an analytical framework to dissect Ustadz Felix Siauw’s communication strategies. The research findings indicate that Ustadz Felix Siauw effectively integrates all six politeness maxims in his communication style, with particular emphasis on the tact maxim and agreement maxim to build rapport with heterogeneous audiences. His logical, communicative, and polite da'wah approach reflects a deep understanding of linguistic pragmatics in the context of modern Islamic preaching. This study concludes that the application of Leech’s politeness maxims not only enhances the effectiveness of da'wah message delivery but also creates an inclusive dialogue space that respects the diverse perspectives of the audience. The implications of this research highlight the importance of pragmatic competence in digital da'wah communication to reach critical and dynamic young Muslim generations.